IMPROVING MOTIVATION TO LEARN USING THE KAHOOT APPLICATION IN TENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 1 SURAKARTA - Ayu Perdanasari (Universitas Muhammadiyah Semarang, 2021)
This study aims to determine the use of the Kahoot application to improve the learning outcomes of students in tenth grade students of SMA Muhammadiyah 1 Surakarta. This research is a classroom action research conducted in two cycles, with research procedures for each cycle covering four activities, namely: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting. The research subjects were students of tenth grade. The data sources came from informants and documents. The data collection of learning motivation was done by using observation, interview and questionnaire techniques. Validity test using triangulation method. Data analysis used descriptive statistics and interactive models for qualitative data. The research performance indicator is set at 85%. The results showed that the use of the Kahoot application could increase students' learning motivation. Student learning motivation in the first cycle is known from the questionnaire results of 77.57%, in the second cycle the questionnaire results show 88.04%.Keywords: learning, motivation, kahoot